Analisis Problematika Guru Penjaskes dalam Memodifikasi Media Pembelajaran PJOK SD Gugus I Kecamatan Ulaweng Kabupaten Bone - Fiana Tami Putri; Muliadi Muliadi; Sudarto Sudarto (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
The problem in this study is to find out the problems of Physical Education teachers in modifying PJOK learning media in Gugus I Elementary School, Ulaweng District, Bone Regency. This research is a descriptive qualitative research. The data analysis technique used three stages, namely data reduction, presentation and drawing of conclusions. The data shows that the modification of PJOK learning media in SD Cluster I, Ulaweng District is modified using simple materials that are easily obtained by teachers. The obstacles for Physical Education teachers in modifying learning media are that it requires a lot of time, effort and lack of teacher skills in designing and making modified media. The conclusions from the results of this study are that in general, Physical Education teachers in Cluster I have made modified media from simple materials, but in modifying the media there are obstacles, namely physical education teachers are less skilled in designing and making media, the cost of making media has not been prepared by the school, and limited time to make media. media for PJOK teachers.Â